(untitled) (World Economics and Finance Bulletin, 2024)
The study aimed to identify the continuous audit approach and its impact on improving the media content of financial reports. This was done by conducting a field study on a sample of Iraqi banks using SPSS to test the study hypotheses. The study found that there is a statistically significant correlation and significant effect between continuous auditing and improving the media content of financial reports at a significant level (0.01), Which helps investors make sound decisions. The study recommended the need for banks’ boards of directors to support internal audit systems by adopting the continuous audit approach because of its positive effects on the accuracy and reliability of immediate information, which reflects positively on the media content of financial reports.